STUDI PENERIMAAN KONSUMEN TERHADAP CLAM FINGER DENGAN FORMULASI BATTER YANG BERBEDA - lucia_dewi lucia_dewi; erpiani_Siregar erpiani_Siregar; abd_sakura abd_sakura (Berkala Perikanan Terubuk, 2018)
Clam Finger (Fish Stick) products from Lingula Unguis have never been done before. During this, the product Finger (Fish Stick) only made from fish, meat and chicken. The production of abundant Lingula Unguis in Tanjung Balai City requires innovative food processing ready to eat and economic value. The purpose of this research is to know how far consumer acceptance to clam finger with different batter formulation. The research method used is the method of expriment with 3 treatments and 3 repetitions. Treatment of A1 (wheat flour and rice flour), A2 (tapioca flour and rice flour), and A3 (rice flour and meizena flour). The research design used was complete randomized design (RAL) non factorial. Organoleptic test results to 80 panelists known to panelists prefer treatment A3 in terms of taste and texture. As many as 27.5% say very like and 62.5% say likes in the flavor category. While 25% states are very fond of texture A3, and as many as 68.75% say likes. From the results of duncan test conducted for the category of appearence and aroma there is no real difference between treatments, while the taste and texture category there is a real difference between A3 and other treatments with 95% confidence level